2006
DOI: 10.1089/ars.2006.8.1757
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Signaling in Plants

Abstract: The evolution of aerobic metabolism such as respiration and photosynthesis resulted in the generation of reactive oxygen species (ROS). A common property of all ROS types is that they can cause oxidative damage to proteins, DNA, and lipids. This toxicity of ROS explains the evolution of complex arrays of nonenzymatic and enzymatic detoxification mechanisms in plants. However, increasing evidence indicates that plants also make use of ROS as signaling molecules for regulating development and various physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(174 citation statements)
references
References 73 publications
4
164
0
6
Order By: Relevance
“…In Arabidopsis, the accumulation of the zinc finger protein ZAT10 promotes the expression of ascorbate POD (APX2; Mittler et al, 2006), while ZAT12 is required for APX1 expression (Rizhsky et al, 2004). APX is one of the most important ROS-scavenging enzymes in plants (Pitzschke et al, 2006). Pro accumulation is a common plant response to a wide range of biotic and abiotic stresses (Verbruggen and Hermans, 2008).…”
Section: Tachp Enhances Salinity Tolerance By Acting On Antioxidationmentioning
confidence: 99%
“…In Arabidopsis, the accumulation of the zinc finger protein ZAT10 promotes the expression of ascorbate POD (APX2; Mittler et al, 2006), while ZAT12 is required for APX1 expression (Rizhsky et al, 2004). APX is one of the most important ROS-scavenging enzymes in plants (Pitzschke et al, 2006). Pro accumulation is a common plant response to a wide range of biotic and abiotic stresses (Verbruggen and Hermans, 2008).…”
Section: Tachp Enhances Salinity Tolerance By Acting On Antioxidationmentioning
confidence: 99%
“…Compelling data supporting the coexistence of redox regulatory pathways and ROS formation in chloroplasts (Apel and Hirt, 2004;Pitzschke et al, 2006;Miller et al, 2008;Foyer and Noctor, 2009) promoted the notion that ROS might be used for regulatory protein oxidation (Apel and Hirt, 2004;Møller et al, 2007). Studies of bacteria, plants, and animals revealed that ROS signals could be perceived directly by specific sensors (Storz et al, 1990;D'Autréaux and Toledano, 2007) or by the use of antioxidative enzymes, such as peroxiredoxins (Prxs) (D'Autréaux and Toledano, 2007;Fourquet et al, 2008;Dietz, 2011;Fomenko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While relatively little is known about the primary receptors that sense these stresses, several downstream signaling cascades have been identified and studied in detail. Stresses may lead to an increase in reactive oxygen species (ROS), cytosolic Ca 2+ or inositol phosphates, which in turn can induce signaling events further downstream (Allen et al, 2000;Xiong et al, 2002;Apel and Hirt, 2004;Gao et al, 2004;Pitzschke et al, 2006). Transmission of these signals includes post-translational modifications such as phosphorylation, ubiquitination and sumoylation of important regulatory factors (Halfter et al, 2000;Dong et al, 2006;Miura et al, 2007).…”
Section: Introductionmentioning
confidence: 99%